Facility Factors Affecting the Uptake and Utilization of Antenatal Care Services By Pregnant Adolescents in Rongai Sub County, Nakuru County.Kenya - Otwori, Daniel A.; Abong'o, Benard; Wanga, Rose (International Journal of Health, Medicine and Nursing Practice, 2023)
Purpose: Antenatal care plays a crucial role in fostering a sense of trust and rapport between the expectant woman and her healthcare practitioner. It serves as a platform for tailoring health promotion messages to the specific needs of the person, while also facilitating the identification and appropriate management of any maternal problems or risk factors that may arise. Complications arising from pregnancy and childbirth constitute the primary cause of mortality among women aged 15-19 years in poor and middle income nations. The objective of this study was to examine the extent to which adolescent mothers in Rongai Sub County, Nakuru County, Kenya utilize antenatal care services. The researchers obtained ethical permission from the GLUK Ethics committee, NACOSTI, and the Nakuru County Government. In addition, the researchers sought consent from the participants and ensured confidentiality by refraining from utilizing any form of identifying. Methodology: The research employed a descriptive cross-sectional study design, utilizing purposeful sampling and single population proportion approaches. The target population comprised of adolescent moms between the ages of 15 and 19 within the geographical area of Rongai Sub County. The data collection instruments employed in this study consisted of researcher-administered questionnaires. The survey was distributed to adolescent mothers who satisfied the specified criteria for inclusion. The acquired data underwent coding and was thereafter fed into the computer system for analysis utilizing SPSS version 25. Findings: The findings of the research were succinctly presented through the utilization of percentages, tables, and charts. There was a significant correlation between adolescents' negative attitudes toward ANC utilization and the results of the study (Ï‡2 =26.306, p =.002). it was also noted that the relationship between hours of operation and adolescents' uptake of ANC was also significant (Ï‡2 =25.865, p =.000). Similarly long waiting hours (Ï‡2 =12.391, p =.054), lack of trust among ANC service providers (Ï‡2 =127.847, p =.000), and high transport cost (Ï‡2 =15.169, p =.019), significantly affected adolescents' uptake of ANC services. Unique Contribution to Theory, Practice and Policy: The findings of this research demonstrate that the utilization of ANC services by adolescent and adult expectant women can offer significant contributions to the understanding of disparities, identification of barriers, and development of appropriate interventions to increase ANC service utilization. It is suggested by this study that tailored services be implemented with the aim of increasing ANC utilization among adolescent mothers in Rongai Sub County.